Streptococcus pneumoniae isolates in healthy children attending day-care centers in 12 states in Mexico Aislamientos de S. pneumoniae en niños sanos de estancias infantiles en 12 estados de México - Luz Elena Espinosa-de los Monteros; Verónica Jiménez-Rojas; Felipe Aguilar-Ituarte; Miguel Cashat-Cruz; Alfonso Reyes-López; Romeo Rodríguez-Suárez; Pablo Kuri-Morales; Roberto Tapia-Conyer; Demóstenes Gómez-Barreto (Instituto Nacional de Salud Pública, 2007)
OBJECTIVE: The aim of this study was to determine the prevalence of asymptomatic nasopharyngeal carriage of Streptococcus pneumoniae, which is a major factor in the transmission of this bacterium. MATERIAL AND METHODS: Nasopharyngeal cultures were performed on children attending 32 day-care centers in 12 states in Mexico. RESULTS: Streptococcus pneumoniae was isolated from the nasopharynx of 829 out of 2 777(29.9%) subjects aged two months to six years. All children lived in urban areas and 80% spent more than six hours daily in a day-care center. Streptococcus pneumoniae serotypes most frequently identified were: 19F (23%), 6B (15.6%), 23F (11.2%) and 6A (14.9%). Thirty-six percent of the isolates were susceptible to penicillin. CONCLUSIONS: Serotype distribution suggests the possible benefits that could be obtained from the heptavalent pneumococcal conjugate vaccine. OBJETIVO: La intención de este estudio fue determinar la prevalencia de portadores nasofaríngeos asintomáticos de Streptococcus pneumoniae, el cual es el principal factor en la transmisión de esta bacteria. MATERIAL Y MÉTODOS: Los cultivos nasofaríngeos fueron realizados en niños que asisten a 32 estancias infantiles en 12 estados de México. RESULTADOS: Streptococcus pneumoniae fue aislado de la nasofaringe de 829 (29.9%) niños de los 2 777 incluidos en el estudio con un rango de edad de 2 meses a 6 años. Todos los niños vivían en áreas urbanas y 80% permanecían más de seis horas diarias en la estancia infantil. Los serotipos de Streptococcus pneumoniae más frecuentemente identificados fueron: 19F (23%), 6B (15.6%), 23F (11.2%) y 6 A (14.9%). Treinta y seis por ciento de los aislamientos fueron susceptibles a penicilina. CONCLUSIONES: La distribución de serotipos nos da una idea de los posibles beneficios que podrían obtenerse de la vacuna neumocóccica conjugada heptavalente.